Energy transfer in reactive movements as a function of individual stretch load - Waldvogel, Janice; Freyler, Kathrin; Ritzmann, Ramona; Gollhofer, Albert (Frontiers in Physiology, 2023)
By directly recording electromyographic activity and muscle-tendon interaction, this study aimed to elucidate the mechanisms why well-trained track and field athletes (experts) are able to outperform untrained individuals without former systematic experience in reactive jump training (novices). In particular, reactive power output and the elastic recoil properties of the muscle-tendon unit were (MTU) of special interest. For this purpose, stiffness regulation on muscle and joint level, and energy management in terms of storing or dissipating energy was compared between experts and novices during various stretch loads. Experts were compared with novices during reactive drop jumps (DJ) from drop heights ranging between 25 and 61 cm. Delta kinetic energy (Ekin) was calculated as the difference between the Ekin at take-off and GC to determine energy management. By recording electromyography of the lower limb muscles, in vivo fascicle dynamics (gastrocnemius medialis) and by combining kinematics and kinetics in a 3D inverse dynamics approach to compute ankle and knee joint kinetics, this study aimed to compare reactive jump performance, the neuromuscular activity and muscle-tendon interaction between experts and novices. Experts demonstrated significantly higher power output during DJ. Among all drop heights experts realized higher delta Ekin compared to novices. Consequently, higher reactive jump performance shown for experts was characterized by shorter ground contact time (GCT), higher jump heights and neuromuscular activity during the GC phase. Concomitantly experts were able to realize highest leg stiffness and delta Ekin in the low stretch loads; however, both groups compensated the highest stretch load by prolonged GCT and greater joint flexion. On muscle level, experts work quasi-isometrically in the highest stretch load, while in novices GM fascicles were forcefully stretched. Group-specific stiffness regulation and elastic recoil properties are primarily influenced by the neuromuscular system. Due to their higher neuromuscular activity prior and during the GC phase, experts demonstrate higher force generating capacity. A functionally stiffer myotendinous system through enhanced neuromuscular input enables the experts loading their elastic recoil system more efficiently, thus realizing higher reactive power output and allowing higher amount of energy storage and return. This mechanism is regulated in a stretch load dependent manner.